Electrochemical Synthesis of Quinolinic Acid from Quinoline - N. Gupta, P.; M. Rather, G. (Asian Journal of Chemistry, 2010)
Proposed mechanism of conversion of quinoline to quinolinic acid involves 16 e transfer reaction, substantiated by millicoulometry. Effects of electrode material, temperature, concentration of both substrate and anolyte on potentiostatic oxidation revealed high efficiency of Pb/PbO2 in 70% H2SO4 at 60ºC.